Intravenous immunoglobulin (IVIg) dampens neuronal toll-like receptor-mediated responses in ischemia - Lok, Ker Zhing (J Neuroinflammation, 2015)
BACKGROUND: Ischemic stroke causes a high rate of deaths and permanent neurological damage in survivors. Ischemic stroke triggers the release of damage-associated molecular patterns (DAMPs) such as high-mobility group box 1 (HMGB1), which activate toll-like receptors (TLRs) and receptor for advanced glycation endproducts (RAGE) in the affected area, leading to an exaggerated inflammatory response and cell death. Both TLRs and RAGE are transmembrane pattern recognition receptors (PRRs) that have been shown to contribute to ischemic stroke-induced brain injury. Intravenous immunoglobulin (IVIg) preparations obtained by fractionating human blood plasma are increasingly being used as an effective therapeutic agent in the treatment of several inflammatory diseases. Its use as a potential therapeutic agent for treatment of stroke has been proposed, but little is known about the direct neuroprotective mechanisms of IVIg. We therefore investigate whether IVIg exerts its beneficial effects on the outcome of neuronal injury by modulating HMGB1-induced TLR and RAGE expressions and activations. METHODS: Primary cortical neurons were subjected to glucose deprivation or oxygen and glucose deprivation conditions and treated with IVIg and recombinant HMGB1. C57/BL6J mice were subjected to middle cerebral artery occlusion, followed by reperfusion, and IVIg was administered intravenously 3 h after the start of reperfusion. Expression of TLRs, RAGE and downstream signalling proteins in neurons and brain tissues were evaluated by immunoblot. RESULTS: Treatment of cultured neurons with IVIg reduced simulated ischemia-induced TLR2, TLR4, TLR8 and RAGE expressions, pro-apoptotic caspase-3 cleavage and phosphorylation of the cell death-associated kinases such as c-Jun N-terminal kinase (JNK), p38 mitogen-activated protein kinase (MAPK) as well as the p65 subunit of nuclear factor kappa B (NF-κB). These results were recapitulated in an in vivo model of stroke. IVIg treatment also upregulated the anti-apoptotic protein B-cell lymphoma 2 (Bcl-2) in cortical neurons under ischemic conditions. Finally, IVIg protected neurons against HMGB1-induced neuronal cell death by modulating TLR and RAGE expressions and signalling pathways. CONCLUSIONS: Taken together, these results provide a rationale for the potential use of IVIg to target inappropriately activated components of the innate immune system following ischemic stroke.